"TIRU" Learning Model Design for Learning in Indonesian Character in Primary School - Maria Ratna Ayu (International Journal of Educational Dynamics, 2019)
In this article writer presentates design of TIRU Learning Model. It is a product of writer’s creation and inovation which will be applied for meaningful and fruitful learning. TIRU model is a model modified from Appreciative Inquiry. Its procedure is Temukan (Discovery), Impikan (Dream), Rancangkan (Design), and Ungkapkan (Delivery/Destiny). For applying writer composes a model implementation for Indonesia Language learning for Class Two.